The Efforts Of Toddler Integrated Healthcare Center Cadres In Increasing Mother Visits To Integrated Healthcare Center Kartini Bandungrejosari Malang City - Handy Lala; Regita Lafemme Rania; Ganif Djuwadi (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2024)
Background: One of the factors causing stunting is that the utilization rate of healthcare by mothers of toddlers in Indonesia is low, while in healthcare there is a lot of education about maintaining the health of toddlers and providing additional food for toddlers. This is proven by the average percentage of toddlers who are weighed at the healthcare is still below the target, where the target for toddlers who are weighed is 85%. There are still many healthcare that do not meet coverage shows that the role of toddler healthcare cadres in increasing mother’s visit to the healthcare less than optimal or not in accordance with their duties. Objectives: The purpose of this study was to determine the efforts of healthcare toddler cadres in increasing maternal visits to the healthcare. Research Metodes: This study used qualitative methods and took 13 responden, consisting of 7 healthcare cadres, 5 mothers who have toddlers, and 1 health worker. Data collection techniques using interviews, observation, documentation. Data validity used is data triangulation and method triangulation. Results: The results show that the implementation of healthcare service activities is still not optimal, this is evidenced by the non-implementation of one of the healthcare service activities. Conclusion: the efforts of cadres in increasing the visit of mothers of toddlers to Healthcare Kartini in Bandungrejosari Village, Sukun Subdistrict still not implemented optimally.